Recommendations on Measuring Hazardous Events and Disasters - Nations Unies (United Nations, 2020)
The Recommendations clarify the role of national statistical offices and other members of national statistical systems in providing information related to hazardous events and disasters, and identify practical steps needed for these organisations, in coordination with national agencies responsible for disaster risk management, to better support disaster risk management efforts. The Recommendations have been prepared by the UNECE Task Force on Measuring Extreme Events and Disasters, composed of Armenia, Italy (Chair), New Zealand, Republic of Moldova, Mexico, South Africa and Turkey, and the following international organisations: UN ECLAC; European Space Agency (ESA), Eurostat, FAO, Joint Research Centre of the European Commission, UNECE, UN ESCAP, UNISDR, WHO and the World Meteorological Organization (WMO). Furthermore, the Group on Earth Observations (GEO) participated in the work of the Task Force.